Siloxane-based heat-conducting antistatic material and preparation method thereof

Through the synergistic effect of epoxy-terminated diphenyltrisiloxane and polyaniline-modified graphene oxide, a three-dimensional thermal conductive network is constructed, and the quaternary ammonium salt groups and imidazoline groups in the antistatic agent are used to provide a stable conductive path, which solves the problems of static electricity accumulation in thermal conductive materials and insufficient thermal conductivity of antistatic materials, and achieves efficient thermal conductivity and antistatic effects and good tensile properties.

CN120699391AActive Publication Date: 2025-09-26广东宝粒金新材料科技有限公司

Patent Information

Application Number
CN202511050390.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-29
Publication Date
2025-09-26
Estimated Expiration
2045-07-29

AI Technical Summary

Technical Problem

Existing thermal conductive materials are prone to static electricity accumulation, and anti-static materials have insufficient thermal conductivity, making it difficult to meet the needs of scenarios such as high-frequency chips and battery modules.

Method used

Epoxy-terminated diphenyltrisiloxane, antistatic agent and polyaniline-modified graphene oxide work synergistically to construct a three-dimensional thermal conductive network, and provide a stable conductive path through quaternary ammonium salt groups and imidazoline groups to enhance the interface bonding and tensile properties of the material.

Benefits of technology

It significantly improves the thermal conductivity and anti-static effect of the material, while also improving the tensile and mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120699391A_ABST
    Figure CN120699391A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polymer composite materials, and discloses a siloxane-based heat-conducting antistatic material and a preparation method thereof. Comprising the following components in parts by weight: 70-80 parts by weight of bisphenol A epoxy resin E51, 3-5 parts by weight of epoxy-terminated diphenyl trisiloxane, 15-20 parts by weight of a methylhexahydrophthalic anhydride curing agent, 3-6 parts by weight of an antistatic agent, 5-8 parts by weight of polyaniline-modified graphene oxide, 0.4-0.6 part by weight of citric acid, 0.1-0.2 part by weight of 2, 4, 6-trimethyl-1, 3-pentanediol monoisobutyrate, 0.1-0.2 part by weight of an antioxidant, 0.1-0.2 part by weight of a coupling agent, 0.1-0.2 part by weight of a coupling agent, and 0.1-0.2 part by weight of a coupling agent. The invention discloses a 2, 6-tri (dimethylaminomethyl) phenol accelerant. The siloxane-based heat-conducting anti-static material disclosed by the invention has relatively good heat-conducting, anti-static and stretching effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer composite materials, in particular to a silicone-based thermally conductive antistatic material and a preparation method thereof. Background Art

[0002] As electronic devices advance towards higher integration and miniaturization, there is an urgent need for materials with synergistic thermal conductivity and anti-static properties. Traditional thermal conductive materials (such as metals and graphite) offer excellent thermal conductivity but are prone to static electricity accumulation. Anti-static materials (such as carbon black-doped polymers) can conduct static electricity but generally have low thermal conductivity, making them inadequate for applications such as high-frequency chips and battery modules. Thermal greases often enhance thermal conductivity by adding metal particles (such as silver powder), but this poses the risk of excessive conductivity and short circuits. Anti-static plastics are doped with carbon black, but the carbon black tends to agglomerate, leading to uneven dispersion. For example, patent CN108912687A discloses an anti-static material for computers and its preparation method. While this invention offers good anti-static properties, its thermal conductivity remains unchanged. Therefore, there is an urgent need to develop a silicone-based composite material that combines high thermal conductivity, controllable anti-static properties, and stable processing. Summary of the Invention

[0003] Technical problems solved In view of the shortcomings of the existing technology, the present invention provides a silicone-based thermally conductive antistatic material and a preparation method thereof, which has good thermal conductivity, antistatic and stretching effects. Technical Solution

[0004] To achieve the above objectives, the present invention provides the following technical solution: a siloxane-based thermally conductive antistatic material, comprising the following components by weight: 70-80 parts by weight of bisphenol A epoxy resin E51, 3-5 parts by weight of epoxy-terminated diphenyltrisiloxane, 15-20 parts by weight of methylhexahydrophthalic anhydride curing agent, 3-6 parts by weight of antistatic agent, 5-8 parts by weight of polyaniline-modified graphene oxide, 0.4-0.6 parts by weight of citric acid, and 0.1-0.2 parts by weight of 2,4,6-tris(dimethylaminomethyl)phenol accelerator.

[0005] Furthermore, the preparation method of the antistatic agent is: S1. Under a nitrogen atmosphere, lauric acid and diethylenetriamine were added to a reactor, stirred and mixed, and heated to 125-130°C. At this time, water vapor began to appear in the reactor. The vacuum pump was started to adjust the vacuum degree of the reaction system to 0.05-0.07 MPa. The temperature was continued to rise to 140-160°C and the reaction was carried out for 2-3 hours. Then, the temperature was raised to 205-210°C and the reaction was carried out for 4-4.2 hours. After the reaction, the mixture was cooled to 115-120°C, poured out, and then cooled to room temperature to obtain a lauryl imidazoline intermediate. S2. The lauryl imidazoline intermediate was added to a reactor containing isopropanol solvent and heated to 76-80°C. A 16% by mass sodium chloroacetate solution was then added. During the reaction, the pH of the reaction system was adjusted to between 8 and 8.5 with a 5% by mass sodium hydroxide solution. The reaction was kept at this temperature for 3-4 hours. After completion, the reaction was subjected to reduced pressure distillation, the product was poured out while hot, and cooled to obtain a quaternary ammonium salt-modified amino imidazoline. S3. To 60-70mL of N,N-dimethylformamide solvent was added 3-5mmol of quaternary ammonium salt-modified amino imidazoline and 3.4-5.4mmol of 4-vinylbenzoyl chloride, stirred and dissolved, and 0.2-0.3mmol of pyridine catalyst was added, and the reaction was allowed to proceed at room temperature. After completion of the reaction, vacuum distillation was performed and filtered to obtain an alkenyl-modified quaternary imidazoline; S4. Under a nitrogen atmosphere, 60-75mL of anhydrous ethanol, 8-10mmol of methacryloyloxyethyltrimethylammonium chloride, 4-6mmol of styrene, 4-7mmol of hydroxyethyl methacrylate, and 2-3mmol of olefin-modified quaternized imidazoline were added to the reactor in sequence, stirred and mixed at room temperature, and then 0.04-0.05g of initiator was added, the temperature was raised to 70-75°C, and the reaction was carried out for 6-7h. After the reaction, the mixture was cooled to room temperature, rotary distilled, and the solvent was removed. The concentrated solution was then added dropwise to toluene for precipitation. The precipitated product was placed in a vacuum drying oven at 80°C and dried for 25h to obtain an antistatic agent.

[0006] Furthermore, the molar ratio of lauric acid to diethylenetriamine in S1 is 3 mmol:3.6-3.9 mmol.

[0007] Furthermore, the usage ratio of the lauryl imidazoline intermediate, isopropyl alcohol, and sodium chloroacetate solution in S2 is 2-2.2 mmol: 50-65 mL: 4-4.5 mmol.

[0008] Furthermore, the reaction time in S3 is 4-7 hours.

[0009] Furthermore, the stirring speed in S4 is 200-210 rpm.

[0010] Furthermore, the initiator in S4 is azobisisobutyronitrile.

[0011] Furthermore, the preparation method of the silicone-based thermally conductive antistatic material is as follows: bisphenol A epoxy resin E51, epoxy-terminated diphenyl trisiloxane, an antistatic agent, polyaniline-modified graphene oxide, and citric acid are added to a reactor, preheated at 60-70°C for 10-15 minutes, then methyl hexahydrophthalic anhydride curing agent is added, stirred at 50-55°C for 4-5 minutes, 2,4,6-tris(dimethylaminomethyl)phenol accelerator is continuously added, stirred for another 5-7 minutes, and then vacuum degassed at 55-60°C for 25-30 minutes to obtain the silicone-based thermally conductive antistatic material.

[0012] Beneficial technical effects The present invention, through the synergistic effect of epoxy-terminated diphenyl trisiloxane, antistatic agent and polyaniline-modified graphene oxide, builds a three-dimensional heat-conducting network, significantly improving heat conduction efficiency. Modified graphene oxide acts as a "bridge" to strengthen the interface bonding between filler and matrix, and graphene oxide itself has good heat conduction and electrical conductivity. The quaternary ammonium salt group and imidazoline group in the antistatic agent synergize with the polyaniline conductive network to provide a stable conductive path, avoid static accumulation, and have good antistatic effect. Bisphenol A type epoxy resin E51 provides a rigid skeleton of the material and crosslinks with the antistatic agent and polyaniline-modified graphene oxide to form a crosslinked network, making its connection more dense, enhancing its tensile properties, and having good mechanical effect. The imidazoline group in the antistatic agent also participates in the epoxy resin curing and the curing agent in the material to form a curing system, thereby increasing compatibility with each other. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is the reaction process of quaternary ammonium salt modifying amino imidazoline. DETAILED DESCRIPTION

[0014] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. All other embodiments derived by persons of ordinary skill in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0015] In order to better understand the above technical solution, the above technical solution will be described in detail below with reference to the accompanying drawings and specific embodiments.

[0016] Epoxy-terminated diphenyl trisiloxane (Zhejiang Yingke New Materials Co., Ltd.) has the following structure: Preparation of polyaniline-modified graphene oxide reference "Study on the anti-corrosion and antistatic properties of modified graphene oxide / polyaniline composites reinforced waterborne polyurethane coatings" S1. 0.05 g of graphene oxide (GO) was placed in 50 mL of PBS buffer and ultrasonically stirred for 3 h to form a uniform 1 mg / mL GO dispersion. The GO dispersion was then heated to 90°C in a water bath, and polyetheramine (PEA) (PEA:GO mass ratio of 10:1) was added dropwise while stirring. After sufficient reaction, a modified GO solution was obtained. The solution was allowed to stand and then centrifuged until the supernatant was neutral. The supernatant was removed and re-dispersed in deionized water by ultrasonication to obtain a modified graphene oxide (AGO) dispersion. S2. Prepare a 1 mol / L 2-acrylamido-2-methylpropanesulfonic acid solution as the doping acid system. Take two 20 mL portions of 2-acrylamido-2-methylpropanesulfonic acid solution, add aniline to one portion to form Solution A, and add ammonium persulfate to the other portion to form Solution B, maintaining a ratio of n(aniline):n(ammonium persulfate) = 0.8:1. Use a magnetic stirrer to mix the two solutions in an ice-water bath. Slowly pour a certain amount of the AGO dispersion into Solution A. After stirring again, slowly add Solution B to Solution A using a rubber-tipped pipette. After complete addition, maintain uniform mixing in an ice-water bath for 6 hours, then allow to rest at room temperature for 24 hours. Demulsify the resulting product with acetone, stir, and then wash with ethanol and deionized water until neutral. Freeze-dry to obtain polyaniline-modified graphene oxide. Example 1

[0017] S1. Under a nitrogen atmosphere, 3 mmol of lauric acid and 3.6 mmol of diethylenetriamine were added to a reactor, stirred and mixed, and heated to 125°C. At this time, water vapor began to appear in the reactor. The vacuum pump was started to adjust the vacuum degree of the reaction system to 0.05 MPa. The temperature was continued to rise to 140°C and the reaction was continued for 2 h. Then, the temperature was raised to 205°C and the reaction was continued for 4 h. After the reaction, the mixture was cooled to 115°C, poured out, and then cooled to room temperature to obtain the lauryl imidazoline intermediate. S2. 2 mmol of the lauryl imidazoline intermediate was added to a reactor containing 50 mL of isopropanol solvent and heated to 76°C. Then, 4 mmol of a 16% sodium chloroacetate solution was added. During the reaction, the pH of the reaction system was adjusted to 8 with a 5% sodium hydroxide solution. The reaction was kept at this temperature for 3 hours. After completion, the reaction was subjected to reduced pressure distillation, the product was poured off while hot, and cooled to obtain a quaternary ammonium salt-modified amino imidazoline. S3. To 60 mL of N, N-dimethylformamide solvent was added 3 mmol of quaternary ammonium salt-modified amino imidazoline and 3.4 mmol of 4-vinylbenzoyl chloride, stirred and dissolved, and 0.2 mmol of pyridine catalyst was added, and the reaction was allowed to proceed at room temperature for 4 h. After the reaction, the mixture was distilled under reduced pressure and filtered to obtain an olefin-modified quaternary imidazoline; S4. Under a nitrogen atmosphere, 60 mL of anhydrous ethanol, 8 mmol of methacryloyloxyethyltrimethylammonium chloride, 4 mmol of styrene, 4 mmol of hydroxyethyl methacrylate, and 2 mmol of olefin-modified quaternized imidazoline were added to the reactor in sequence, stirred and mixed at room temperature at a stirring speed of 200 rpm, and then 0.04 g of azobisisobutyronitrile was added. The temperature was raised to 70°C and the reaction was carried out for 6 h. After the reaction was completed, the mixture was cooled to room temperature and rotary distilled to remove the solvent. The concentrate was then added dropwise to toluene for precipitation. The precipitated product was dried in a vacuum drying oven at 80°C for 25 h to obtain an antistatic agent. S5. Add 70 parts by weight of bisphenol A epoxy resin E51, 3 parts by weight of epoxy-terminated diphenyltrisiloxane, 3 parts by weight of antistatic agent, 5 parts by weight of polyaniline-modified graphene oxide, and 0.4 parts by weight of citric acid into a reactor, preheat at 60°C for 10 minutes, then add 15 parts by weight of methylhexahydrophthalic anhydride curing agent, stir at 50°C for 4 minutes, continue to add 0.1 parts by weight of 2,4,6-tris(dimethylaminomethyl)phenol accelerator, stir for another 5 minutes, and then vacuum degas at 55°C for 25 minutes to obtain a silicone-based thermally conductive antistatic material. Example 2

[0018] S1. Under a nitrogen atmosphere, 3 mmol of lauric acid and 3.9 mmol of diethylenetriamine were added to a reactor, stirred and mixed, and heated to 130°C. At this time, water vapor began to appear in the reactor. The vacuum pump was started to adjust the vacuum degree of the reaction system to 0.07 MPa. The temperature was continued to rise to 160°C and the reaction was continued for 3 hours. Then, the temperature was raised to 210°C and the reaction was continued for 4.2 hours. After the reaction, the mixture was cooled to 120°C, poured out, and then cooled to room temperature to obtain the lauryl imidazoline intermediate. S2. 2.2 mmol of the lauryl imidazoline intermediate was added to a reactor containing 65 mL of isopropanol solvent and heated to 80°C. Then, 4.5 mmol of a 16% sodium chloroacetate solution was added. During the reaction, the pH of the reaction system was adjusted to 8.5 with a 5% sodium hydroxide solution. The reaction was kept at this temperature for 4 hours. After completion, the reaction was vacuum distilled, the product was poured off while hot, and cooled to obtain a quaternary ammonium salt-modified amino imidazoline. S3. To 70 mL of N, N-dimethylformamide solvent was added 5 mmol of quaternary ammonium salt-modified amino imidazoline and 5.4 mmol of 4-vinylbenzoyl chloride, stirred and dissolved, and 0.3 mmol of pyridine catalyst was added, and the reaction was allowed to proceed at room temperature for 7 h. After the reaction, the mixture was distilled under reduced pressure and filtered to obtain an olefin-modified quaternary imidazoline; S4. Under a nitrogen atmosphere, 75 mL of anhydrous ethanol, 10 mmol of methacryloyloxyethyltrimethylammonium chloride, 6 mmol of styrene, 7 mmol of hydroxyethyl methacrylate, and 3 mmol of olefin-modified quaternized imidazoline were added to the reactor in sequence, stirred and mixed at room temperature at a stirring speed of 210 rpm, and then 0.05 g of azobisisobutyronitrile was added. The temperature was raised to 75 ° C. and the reaction was carried out for 7 h. After the reaction was completed, the mixture was cooled to room temperature and rotary distilled to remove the solvent. The concentrate was then added dropwise to toluene for precipitation. The precipitated product was dried in a vacuum drying oven at 80 ° C for 25 h to obtain an antistatic agent. S5. Add 80 parts by weight of bisphenol A epoxy resin E51, 5 parts by weight of epoxy-terminated diphenyltrisiloxane, 6 parts by weight of antistatic agent, 8 parts by weight of polyaniline-modified graphene oxide, and 0.6 parts by weight of citric acid into a reactor, preheat at 70°C for 15 minutes, then add 20 parts by weight of methylhexahydrophthalic anhydride curing agent, stir at 55°C for 5 minutes, continue to add 0.2 parts by weight of 2,4,6-tris(dimethylaminomethyl)phenol accelerator, stir for another 7 minutes, and then vacuum degas at 60°C for 30 minutes to obtain a silicone-based thermally conductive antistatic material. Example 3

[0019] S1. Under a nitrogen atmosphere, 3 mmol of lauric acid and 3.8 mmol of diethylenetriamine were added to a reactor, stirred and mixed, and heated to 127°C. At this time, water vapor began to appear in the reactor. The vacuum pump was started to adjust the vacuum degree of the reaction system to 0.06 MPa. The temperature was continued to rise to 150°C and the reaction was carried out for 2.5 hours. Then, the temperature was raised to 208°C and the reaction was carried out for 4.1 hours. After the reaction, the mixture was cooled to 117°C, poured out, and then cooled to room temperature to obtain the lauryl imidazoline intermediate. S2. 2.1 mmol of the lauryl imidazoline intermediate was added to a reactor containing 60 mL of isopropanol solvent and heated to 78°C. Then, 4.2 mmol of a 16% sodium chloroacetate solution was added. During the reaction, the pH of the reaction system was adjusted to 8.2 with a 5% sodium hydroxide solution. The reaction was kept at this temperature for 3.5 hours. After completion, the reaction was subjected to reduced pressure distillation, the product was poured off while hot, and cooled to obtain a quaternary ammonium salt-modified amino imidazoline. S3. To 65 mL of N, N-dimethylformamide solvent was added 4 mmol of quaternary ammonium salt-modified amino imidazoline and 4.5 mmol of 4-vinylbenzoyl chloride, stirred and dissolved, and 0.25 mmol of pyridine catalyst was added, and the reaction was allowed to proceed at room temperature for 6 h. After the reaction, the mixture was distilled under reduced pressure and filtered to obtain an olefin-modified quaternary imidazoline; S4. Under a nitrogen atmosphere, 70 mL of anhydrous ethanol, 9 mmol of methacryloyloxyethyltrimethylammonium chloride, 5 mmol of styrene, 6 mmol of hydroxyethyl methacrylate, and 2.5 mmol of olefin-modified quaternized imidazoline were added to the reactor in sequence, stirred and mixed at room temperature at a stirring speed of 205 rpm, and then 0.045 g of azobisisobutyronitrile was added. The temperature was raised to 72°C and the reaction was carried out for 6 h. After the reaction was completed, the mixture was cooled to room temperature and rotary distilled to remove the solvent. The concentrate was then added dropwise to toluene for precipitation. The precipitated product was dried in a vacuum drying oven at 80°C for 25 h to obtain an antistatic agent. S5. Add 75 parts by weight of bisphenol A epoxy resin E51, 4 parts by weight of epoxy-terminated diphenyltrisiloxane, 4.5 parts by weight of antistatic agent, 6 parts by weight of polyaniline-modified graphene oxide, and 0.5 parts by weight of citric acid into a reactor, preheat at 65°C for 12 minutes, then add 17 parts by weight of methylhexahydrophthalic anhydride curing agent, stir at 52°C for 4.5 minutes, continue to add 0.15 parts by weight of 2,4,6-tris(dimethylaminomethyl)phenol accelerator, stir for another 6 minutes, and then vacuum degas at 57°C for 28 minutes to obtain a silicone-based thermally conductive antistatic material.

[0020] Comparative Example 1 Compared with Example 3, this comparative example differs in that a lauryl imidazoline intermediate is used instead of the antistatic agent.

[0021] Comparative Example 2 Compared with Example 3, this comparative example is different in that graphene oxide is used instead of polyaniline-modified graphene oxide.

[0022] Performance Testing The surface resistance of each sample of silicone-based thermally conductive antistatic material was tested using ISO 61340-5-1 as the testing standard. Thermal conductivity was tested according to ASTM C1113.

[0023] Table 1: Antistatic and thermal conductivity tests.

[0024]

[0025] As can be seen from Table 1, the siloxane-based thermally conductive antistatic materials prepared in the present invention, Examples 1-3, have better antistatic and thermal conductive effects than Comparative Examples 1-2.

[0026] The tensile properties of the materials were tested using an electronic universal testing machine. The test results are shown in Table 2.

[0027] Table 2: Tensile properties tested.

[0028]

[0029] As can be seen from Table 2, the silicone-based thermally conductive antistatic materials of the present invention, Examples 1-3 have better tensile properties than Comparative Examples 1-2, and therefore have better mechanical properties.

[0030] It should be noted that, in this document, the terms "comprise," "include," or any other variations thereof are intended to encompass non-exclusive inclusion, such that a process, method, article, or apparatus comprising a series of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus. In the absence of further limitations, an element defined by the phrase "comprises a ..." does not preclude the presence of other identical elements in the process, method, article, or apparatus comprising the element.

[0031] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the present invention.

[0032] Those skilled in the art should understand that the above descriptions are only some specific embodiments of the present invention, rather than all embodiments.

Claims

1. A silicone-based thermally conductive antistatic material, characterized in that: The invention comprises the following components by weight: 70-80 parts by weight of bisphenol A epoxy resin E51, 3-5 parts by weight of epoxy-terminated diphenyltrisiloxane, 15-20 parts by weight of methylhexahydrophthalic anhydride curing agent, 3-6 parts by weight of antistatic agent, 5-8 parts by weight of polyaniline-modified graphene oxide, 0.4-0.6 parts by weight of citric acid, and 0.1-0.2 parts by weight of 2,4,6-tris(dimethylaminomethyl)phenol accelerator.

2. The silicone-based thermally conductive antistatic material according to claim 1, characterized in that: The preparation method of the antistatic agent is: S1. Under a nitrogen atmosphere, lauric acid and diethylenetriamine were added to a reactor, stirred and mixed, and heated to 125-130°C. At this time, water vapor began to appear in the reactor. The vacuum pump was started to adjust the vacuum degree of the reaction system to 0.05-0.07 MPa. The temperature was continued to rise to 140-160°C and the reaction was carried out for 2-3 hours. Then, the temperature was raised to 205-210°C and the reaction was carried out for 4-4.2 hours. After the reaction, the mixture was cooled to 115-120°C, poured out, and then cooled to room temperature to obtain a lauryl imidazoline intermediate. S2. The lauryl imidazoline intermediate is added to a reactor containing isopropanol solvent and heated to 76-80°C. A 16% by mass sodium chloroacetate solution is then added. During the reaction, the pH of the reaction system is adjusted to between 8 and 8.5 with sodium hydroxide solution. The reaction is kept at this temperature for 3-4 hours. After completion, the reaction is subjected to reduced pressure distillation, the product is poured out while hot, and cooled to obtain a quaternary ammonium salt-modified amino imidazoline. S3. To 60-70mL of N,N-dimethylformamide solvent was added 3-5mmol of quaternary ammonium salt-modified amino imidazoline and 3.4-5.4mmol of 4-vinylbenzoyl chloride, stirred and dissolved, and 0.2-0.3mmol of pyridine catalyst was added, and the reaction was allowed to proceed at room temperature. After completion of the reaction, vacuum distillation was performed and filtered to obtain an alkenyl-modified quaternary imidazoline; S4. Under a nitrogen atmosphere, 60-75mL of anhydrous ethanol, 8-10mmol of methacryloyloxyethyltrimethylammonium chloride, 4-6mmol of styrene, 4-7mmol of hydroxyethyl methacrylate, and 2-3mmol of olefin-modified quaternized imidazoline were added to the reactor in sequence, stirred and mixed at room temperature, and then 0.04-0.05g of initiator was added, the temperature was raised to 70-75°C, and the reaction was carried out for 6-7h. After the reaction, the mixture was cooled to room temperature, rotary distilled, and the solvent was removed. The concentrated solution was then added dropwise to toluene for precipitation. The precipitated product was placed in a vacuum drying oven at 80°C and dried for 25h to obtain an antistatic agent.

3. The silicone-based thermally conductive antistatic material according to claim 2, characterized in that: The molar ratio of lauric acid to diethylenetriamine in S1 is 3 mmol:3.6-3.9 mmol.

4. The silicone-based thermally conductive antistatic material according to claim 2, characterized in that: The usage ratio of the lauryl imidazoline intermediate, isopropyl alcohol, and sodium chloroacetate solution in S2 is 2-2.2 mmol: 50-65 mL: 4-4.5 mmol.

5. The silicone-based thermally conductive antistatic material according to claim 2, characterized in that: The reaction time in S3 is 4-7 hours.

6. The silicone-based thermally conductive antistatic material according to claim 1, characterized in that: The stirring speed in S4 is 200-210 rpm.

7. The silicone-based thermally conductive antistatic material according to claim 1, characterized in that: The initiator in S4 is azobisisobutyronitrile.

8. A method for preparing the silicone-based thermally conductive antistatic material according to any one of claims 1 to 7, characterized in that: The preparation method of the silicone-based thermally conductive antistatic material comprises the following steps: adding bisphenol A epoxy resin E51, epoxy-terminated diphenyltrisiloxane, an antistatic agent, polyaniline-modified graphene oxide, and citric acid into a reactor, preheating at 60-70° C. for 10-15 minutes, then adding methylhexahydrophthalic anhydride curing agent, stirring at 50-55° C. for 4-5 minutes, continuously adding 2,4,6-tris(dimethylaminomethyl)phenol accelerator, stirring for another 5-7 minutes, and then vacuum degassing at 55-60° C. for 25-30 minutes to obtain the silicone-based thermally conductive antistatic material.

Citation Information

Patent Citations

  • Powder coating comprising graphene / polyaniline composite filler and preparation method of powder coating

    CN107141967A

  • Novel water soluble imidazoline-ammonium-salt corrosion inhibitor and preparation method thereof

    CN110306193A

  • Heat dissipation paint composition and heat dissipation structure

    US20150275061A1

Cited By

  • Graphene modified epoxy resin antistatic material and preparation method thereof

    CN121427255A